2019
DOI: 10.1111/jace.16490
|View full text |Cite
|
Sign up to set email alerts
|

Weakening thermal quenching to enhance luminescence of Er3+ doped β‐NaYF4 nanocrystals via acid‐treatment

Abstract: Rare earth (RE) ions‐doped luminescent nanocrystals (NCs) with numerous unique advantages have attracted tremendous interest for the wide applications from science to engineering, yet suffering from the shortcoming of thermal quenching coming from surface organic ligands. We propose utilizing a facile acid‐base reaction to remove surface organic ligands introduced choosing carboxylic acids as stabilizing agent and weaken thermal quenching. The results showed that the acid‐base reaction displayed an outstanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] Yang et al have reported a facile approach to weaken the thermal quenching procedure for improving upconversion efficiency of Er 3+ -doped β-NaYF 4 nanocrystals via acidtreatment. 10 More exertions should be dedicated to find novel procedures to improve the upconversion performance of the fluorides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Yang et al have reported a facile approach to weaken the thermal quenching procedure for improving upconversion efficiency of Er 3+ -doped β-NaYF 4 nanocrystals via acidtreatment. 10 More exertions should be dedicated to find novel procedures to improve the upconversion performance of the fluorides.…”
Section: Introductionmentioning
confidence: 99%
“…Several research works have been reported on the altering of crystal field using the variation in electric/ magnetic field, doping with a transition metal, and rare‐earth elements to enhance upconversion emission 1‐6 . Yang et al have reported a facile approach to weaken the thermal quenching procedure for improving upconversion efficiency of Er 3+ ‐doped β‐NaYF 4 nanocrystals via acid‐treatment 10 . More exertions should be dedicated to find novel procedures to improve the upconversion performance of the fluorides.…”
Section: Introductionmentioning
confidence: 99%
“…A family of rare earth (RE) elements is considered between the elements of the lanthanide group which shows pronounced biological activity as they are capable of replacing Ca 2+ in investigated glass matrix [1][2]. Most of the recent studies have concentrated on enhancing the bioactivity of glass materials by the effect of RE ions [3][4][5][6][7][8]. These advances include the preparation of special glass materials, or the introduction of certain useful elements in the matrix of the simple glass materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…The research interest in the branch of borate glass systems is due to their anomalous behavior. Borate glass has been studied most recently in contrast with other traditional glasses due to its good optical and mechanical properties [8,10]. Borate glass systems are well known to have a stable structure against ambient humidity, good corrosion resistance in mechanical strength and chemical toughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation